Consensus recommendations for use of maintenance immunosuppression in solid organ transplantation: Endorsed by the American College of Clinical Pharmacy, American Society of Transplantation, and International Society for Heart and Lung Transplantation: An executive summary. Issue 8 (29th August 2022) - Nelson, Joelle; Alvey, Nicole; Bowman, Lyndsey; Schulte, Jamie; Segovia, Maria Cristina; McDermott, Jennifer; Te, Helen S.; Kapila, Nikhil; Levine, Deborah Jo; Gottlieb, Robert L.; Oberholzer, Jose; Campara, Maya
Abstract: Advances in maintenance immunosuppression over the past three decades have improved solid organ transplantation outcomes dramatically. Uninterrupted access to immunosuppression is paramount to minimize rejection and maintain allograft and patient survival. Agents used vary based on transplanted organ, center‐specific protocol, provider expertise, insurance formularies, ability to cover co‐pays, recipient characteristics and tolerability. Published data reflects this heterogeneity. Despite these obstacles, the information about maintenance immunosuppression use cross pollinates between organ groups with standard of care agents often being used off‐label, making medication access a challenge for many transplant recipients. A multidisciplinary panel of American transplant clinicians was formed to review published literature on maintenance immunosuppression with the goal to formulate consensus recommendations for their use in specific organ groups. These consensus recommendations are intended to provide transplant clinicians with a summary of literature on maintenance immunosuppression in the modern era, and to support transplant team members working to secure medication access for patients.